Pårørendes erfaringer med bruk av frivillige ved alvorlig sykdom i hjemmet - Flateland, Sylvi Monika; Skaar, Ragnhild; Fensli, Marthe M.F.; Söderhamn, Ulrika (Nordisk tidsskrift for helseforskning, 2017)
Next-of-kins’ experiences when using volunteers for palliative patients living at home The aim of this study was to illuminate next-of-kins’ experiences when using volunteers supplementing community health care services for palliative patients living at home. The study has a qualitative approach. Nine individual interviews were conducted with next of kin from a municipality in Southern Norway. Use of volunteers for palliative care in the home was a relief for next-of-kin, especially prominent for families who had limited social network. Planned volunteering resulted in the best results. Use of volunteer was also found helpful for families as they were given a "breathing space" and a certain normalization of everyday life. The volunteers followed up activities related to the patient that the next-of-kin to a limited extent managed to attend. This affected the next-of-kin’s conscience in a positive way. The next-of-kin experienced the volunteers to be empathetic, they could inspire confidence and showed good characteristics to assist ill people and their next-of-kin. The next-of-kin needed regular relief from volunteers as a supplement to the community health care services. The volunteers were well suited to meet people, who were in a difficult situation, and with their approach they had strong confidence in the next-of-kin and gave them relief in a challenging environment. The coordinator for palliative care was a key person in relation to the link between families, patients in palliative care and the volunteers.